Quantitative Determination of Lactones in Piper methysticum (Kava-Kava) by Supercritical Fluid Chromatography - Murauer, Adele; Ganzera, Markus (Planta Medica, 2017)
A fast and validated supercritical fluid chromatography method for the quantitative determination of major lactones in Piper methysticum, a plant used against nervous anxiety, stress, and restlessness, was developed. The baseline separation of dihydrokavain, demethoxyyangonin, kavain, yangonin, dihydromethysticin, and methysticin was possible in less than 4 min on an Aquity UPC2 BEH 1.7 µm column, in combination with a mobile phase comprising CO2 and methanol with diethylamine. The column temperature had a great impact on the results because only at 70 °C could kavain and yangonin be fully resolved. With correlation coefficients above 0.998, recovery rates between 95.9 and 104.1 % as well as limit of detection values below 1.5 ng on-column, the procedure fulfilled all validation requirements and was well suited for the quantitative analysis of commercial products containing P. methysticum root powder and/or extract. All of them contained the target analytes, however, the absolute content of lactones was quite variable. Accordingly, depending on the product, the total daily intake of lactones varied from 56 to 312 mg. Concerning speed, selectivity, and environmental friendly operation, this supercritical fluid chromatography approach surpasses all previously reported ones.
Keywords: supercritical fluid chromatography; Piper methysticum; Piperaceae; kavalactones